“Facing the Monolith:” Virginia Woolf, Modernism and Impersonality - Paolo BUGLIANI (E-REA)
This paper aims at investigating Virginia Woolf’s stance on impersonality in literature in relation to the famous “continual extinction of personality” expressed by T. S. Eliot in “Tradition and the Individual Talent.” His reaction against the romantic stereotype of the hypertrophic self was not an entire novelty: the need for an eclipse of the authorial agency on the literary text had already been voiced by Gustave Flaubert, and, perhaps more paradoxically, by John Keats. Woolf’s position in this literary dispute is significant, since she rather openly refused to endorse Eliot’s authorial ostracism, proposing an alternative which followed the principle of “saturation,” implying a bulimic inclusion, rather than a careful selection.This paper shows that it was in her nonfiction that Woolf first articulated a critical reaction to impersonality, developing the concept of “presence,” which lies at the core of her essayistic ideal, in “The Modern Essay.” In addition to that, the statement of a much needed authorial aura in the literary text underlies Woolf’s overwhelming urge for life writing, both in fiction and nonfiction. The genesis of this idea, rooted in ancient Greek literature and most importantly in Montaigne’s essayistic self-portraiture, firmly positions Woolf among the Western expressivist cultural tradition.